`f(x,y) = ln ((x-y)/(x+y)^2)`

`f(x,y) = ln(x-y)-ln(x+y)^2`

`f(x,y) = ln(x-y)-2ln(x+y)`

When we are doing partial derivatives we consider only one changing variable and others are constant.

When you derivate with respect to x we consider y as a constant and derivation with respect to y, x is considered as...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`f(x,y) = ln ((x-y)/(x+y)^2)`

`f(x,y) = ln(x-y)-ln(x+y)^2`

`f(x,y) = ln(x-y)-2ln(x+y)`

When we are doing partial derivatives we consider only one changing variable and others are constant.

When you derivate with respect to x we consider y as a constant and derivation with respect to y, x is considered as constant.

`(delf(x,y))/(delx) = f_x(x,y)`

`(delf(x,y))/(dely) = f_y(x,y)`

`f_x(x,y) = 1/(x-y)-2/(x+y)`

`f_y(x,y) = 1/(x-y)*(-1)-2/(x+y) = (-1)[1/(x-y)+2/(x+y)]`